2022
DOI: 10.1371/journal.pntd.0010363
|View full text |Cite
|
Sign up to set email alerts
|

Berbamine hydrochloride potently inhibits SARS-CoV-2 infection by blocking S protein-mediated membrane fusion

Abstract: COVID-19 caused by SARS-CoV-2 has posed a significant threat to global public health since its outbreak in late 2019. Although there are a few drugs approved for clinical treatment to combat SARS-CoV-2 infection currently, the severity of the ongoing global pandemic still urges the efforts to discover new antiviral compounds. As the viral spike (S) protein plays a key role in mediating virus entry, it becomes a potential target for the design of antiviral drugs against COVID-19. Here, we tested the antiviral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…S1Bb). We also showed that treatment of 293T-ACE2 cells with naringenin, tetrandrine, bafilomycin A1, fangchinoline, or cepharanthine (i.e., previously reported in vitro inhibitors of SARS-CoV-2 infection [ 2 , 19 , 77 , 78 ]) led to a significant inhibition of pseudoviral entry compared with the dimethyl sulfoxide (DMSO) control (Fig. S1C).…”
Section: Resultssupporting
confidence: 61%
“…S1Bb). We also showed that treatment of 293T-ACE2 cells with naringenin, tetrandrine, bafilomycin A1, fangchinoline, or cepharanthine (i.e., previously reported in vitro inhibitors of SARS-CoV-2 infection [ 2 , 19 , 77 , 78 ]) led to a significant inhibition of pseudoviral entry compared with the dimethyl sulfoxide (DMSO) control (Fig. S1C).…”
Section: Resultssupporting
confidence: 61%
“…An earlier report has shown that berbamine inhibits SARS-CoV-2 entry into the target cells by impairing Transient Receptor Potential cation channel, MucoLipin subfamily (TRPMLs)-mediated endolysosomal trafficking of ACE2 ( Huang et al, 2021 ) and could inhibit S-mediated cell-cell fusion. ( Zhang et al, 2022 ). Cepharanthine, a naturally occurring alkaloid extracted from the plant Stephania cepharantha Hayata, has been previously reported to inhibit SARS-CoV-2 binding to target cells and thereby prevent virus entry ( Ohashi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…berbamine hydrochloride is a bis-benzylisoquinoline alkaloid isolated from the traditional Chinese herb Berberis amurensis. Berbaminebe was demonstrated to have antiviral activity against different types of viruses, such as bovine viral diarrhea virus (BVDV), Japanese encephalitis virus (JEV), and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [22][23][24][25]. Moreover, berbamine regulates multiple cellular biological processes.…”
Section: Introductionmentioning
confidence: 99%